IMPLEMENTASI UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 16 TAHUN 2009 TENTANG KETENTUAN UMUM TATA CARA PERPAJAKAN DALAM MENANGGULANGI TINDAK PIDANA DI BIDANG PERPAJAKAN - Mokhamad Rizza A (Scientia Regendi, 2020)
The use of criminal sanctions in Law Number 16 of 2009 concerning General Provisions on Tax Procedures, raises legal issues at the conceptual level. That the Tax Law is part of the State Administrative Law, requires forced efforts for taxpayers, which in principle is a form of criminalization of administrative behavior. The parameter of tax crime is only limited by the element of negligence and deliberation, the application of which is based on the discretion of the competent institution. Resulting in transactional behavior on a practical level. Therefore, the principle of ultimum remedium, it becomes very important to avoid the use of arbitrary discretion. In connection with this matter, there are some interesting issues to study, among others, how is law enforcement by the Civil Servant Investigating Directorate General of Taxes against taxpayers who commit tax crime? and how is the application of tax penalties as ultimum remedium in Act Number 16 of 2009 concerning General Provisions for Tax Procedures? The results of the study concluded that law enforcement by the Civil Servant Investigator of the Directorate General of Taxes against Taxpayers who commit tax crime based on the provisions of Law Number 16 of 2009 concerning General Provisions on Taxation Procedures is causing irony, because in Law Number 16 of 2009 concerning General Provisions on Tax Procedures have a large discretion by the Directorate General of Taxes, in this case the Civil Servant Investigator, to determine whether a violation (in this case a tax crime) should be subject to administrative sanctions or criminal sanctions. The imposition of criminal sanctions in Law Number 16 of 2009 concerning General Provisions on Tax Procedures should not only prioritize the interests of the state, but also prioritize the interests of taxpayers, especially corporate taxpayers, because revenue for the state will benefit all Indonesians, rather than applying penalties . Criminalization in tax law should be the last alternative in applying the law (ultimum remedium principle).